2021
DOI: 10.3390/jdb9030037
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Transcripts of Hox Genes Are Found in Oocytes of Platynereis dumerilii (Annelida, Nereididae)

Abstract: Hox genes are some of the best studied developmental control genes. In the overwhelming majority of bilateral animals, these genes are sequentially activated along the main body axis during the establishment of the ground plane, i.e., at the moment of gastrulation. Their activation is necessary for the correct differentiation of cell lines, but at the same time it reduces the level of stemness. That is why the chromatin of Hox loci in the pre-gastrulating embryo is in a bivalent state. It carries both repressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Our study provides new information suggesting that maternal expression of Ubx and abdA began to evolve (most likely convergently) early in arthropod evolution. Furthermore, maternal transcripts of nine Hox genes were found in oocytes of errant annelid Platynereis dumerilii (Maslakov et al, 2021) and of six Hox genes of different paralogical group has been found in oocytes and preimplantation embryos in mammals (bovine and mice) (Paul et al, 2011), but the roles of these Hox genes in early development are still unknown. Paul et al (2011) suggest that these Hox genes may be related to the control of oocyte maturation in mammals, while Maslakov et al (2021) suggest that these Hox transcripts are not translated and may be necessary for some crucial evolutionary conservative function, such as the epigenetic adjustment of the zygotic genome.…”
Section: Resultsmentioning
confidence: 99%
“…Our study provides new information suggesting that maternal expression of Ubx and abdA began to evolve (most likely convergently) early in arthropod evolution. Furthermore, maternal transcripts of nine Hox genes were found in oocytes of errant annelid Platynereis dumerilii (Maslakov et al, 2021) and of six Hox genes of different paralogical group has been found in oocytes and preimplantation embryos in mammals (bovine and mice) (Paul et al, 2011), but the roles of these Hox genes in early development are still unknown. Paul et al (2011) suggest that these Hox genes may be related to the control of oocyte maturation in mammals, while Maslakov et al (2021) suggest that these Hox transcripts are not translated and may be necessary for some crucial evolutionary conservative function, such as the epigenetic adjustment of the zygotic genome.…”
Section: Resultsmentioning
confidence: 99%
“…teleta [40] and the mollusc P. yessoensis [42]. However, another annelid, Platynereis dumerilii , displayed maternal expression pattern [56]. It remains unclear whether the maternal expression is lost in these three species or whether this maternal expression is an exception.…”
Section: Discussionmentioning
confidence: 99%
“…We used Hox genes of other spiralian species from Genbank: Platynereis dumerilii (Kukalova et al, 2007;Maslakov et al, 2021), Capitella teleta (Frobius et al, 2008), Owenia fusiformis (Martin-Zamora et al, 2023), Crassostrea virginica (Modak et al, 2021) and Lottia goshimai (Huan et al, 2020) to construct a gene phylogeny (Table S2, Supplementary Data1). Amino acid sequences were aligned using MUSCLE which is included in the SEAVIEW software (Edgar, 2004;Gouy et al, 2010).…”
Section: Molecular Phylogenetic Analysesmentioning
confidence: 99%